The Needs of Interdisciplinary Integration in the Educational System (Eurasian Scientific Herald, 2022)
This article describes the existing problems and tasks in the organization of teaching on the basis of interdisciplinary integration in the educational system. Organizing the educational process on the basis of interdisciplinary integration requires the development of methodological recommendations for each subject of the educational material.